Emotional distress in women before and after therapeutic termination of pregnancy: an investigation into the need for pre and post abortion counselling - Forrest, Gillian Moira (Department of Social Development, 2026)
The research is an. exploratory and descriptive study into emotional distress in women, before and after terminations of pregnancy at the Pregnancy Advisory Service at Groote Schuur Hospital, which aims to assess the need for pre- and postabortion counselling. The participants were women seen at the Pregnancy Advisory Service from 1 - 14 December 1993 and 5 - 19 January 1994 and assessed for terminations of pregnancy according to Section 3 Cl)Cb) of the Abortion and Sterilization Act of 1975. The research methods were survey research and participant observation. The results indicated that levels of emotional distress in the short term after termination of pregnancy are much lower than before a termination of pregnancy and as a result most women do not want post-abortion counselling.